Characterizing the adult zebrafish model of Parkinson’s disease: a systematic review of dynamic changes in behavior and physiology post-MPTP administration - Razali, Khairiah; Kumar, Jaya; Mohamed, Wael M. Y. (Frontiers in Neuroscience, 2024)
IntroductionAdult zebrafish are increasingly used in Parkinson’s disease (PD) research due to their well-characterized dopaminergic system. Among the toxin-based models, the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is widely utilized to induce parkinsonism in adult zebrafish. Therefore, this review presents an overview of the procedures and the dynamic changes in behavior and physiology observed in the adult zebrafish PD model following a single intraperitoneal injection of MPTP.MethodsA systematic literature search in the PubMed and Google Scholar databases was conducted to identify relevant articles. Of the 165 articles identified, 9 were included in this review. These chosen articles are original works published before March 2024, all of which utilized adult zebrafish induced with MPTP as the model for PD. Other articles were excluded based on factors such as limited relevance, utilization of zebrafish embryos or larvae instead of adults, and variations in MPTP deliveries.ResultsStudies indicated that the ideal model entails the utilization of mixed gender zebrafish aged between 4 and 6 months from the wild-type strain. The acceptable MPTP doses ranges between 20 μg/g (lowest) and 225 μg/g (highest) and doses above 292 μg/g are lethal. Furthermore, noticeable parkinsonian symptoms appear 1 day after administration and persist for more than 1 week.DiscussionMitochondrial dysfunction precedes dopaminergic neurodegeneration within this experimental regime. A single administration of MPTP effectively induces PD in adult zebrafish. This study aids in crafting the adult zebrafish PD model, outlining the progressive behavioral and physiological changes ensuing from MPTP administration.